EFFICIENCY OF HANDLINE TUNA FISHERMEN’S WORKING TIME USING THE PERT APPROACH - Irawan, Andi; Mardiah, Ratu Sari; Yusrizal; Leilani, Ani; Nugraha, Erick; Febriyanto, Fredi; Miswar, Edi (Marine Fisheries : Journal of Marine Fisheries Technology and Management, 2026)
Handline tuna fishing constitutes one of the key economic activities in coastal areas, particularly for small-scale fishermen. Efficient working time plays a vital role in improving fishermen’s productivity and income. However, in practice, tuna fishing operations frequently encounter inefficiencies in both planning and the execution of daily tasks. Therefore, an analytical method is required to identify and evaluate each stage of the work process systematically. The Program Evaluation and Review Technique (PERT) provide a structured approach to mapping work activities, estimating the time required for each task, and identifying the critical path that determines the total project duration. This study aims to evaluate the efficiency of working time utilization among tuna fishermen using handline gear by applying the PERT approach. The research was conducted on 163 fishing vessels using the PERT (Project Evaluation and Review Technique) method, focusing on the analysis of actual time allocation for each activity. The results indicate that of the 24 analyzed activities, 17 (70.83%) fall within the critical path, while 7 (29.17%) have slack time. Critical activities such as loading supplies, traveling to the fishing ground, and retrieving the parachute anchor determine the project’s minimum duration. Meanwhile, activities with slack time, such as preparing the parachute anchor and mooring the vessel to the fish aggregating device (FAD), can be performed flexibly without affecting the overall project timeline. Effective time management is essential to ensure that each operational phase is completed on schedule, thereby improving the efficiency and productivity of fishing operations. Keywords: critical path, handline, PERT, tuna.